Knowledge and food practices questionnaire: construction and validation - da Silva, Anelise Bozzetto; Piccoli, Ângela B.; Pellanda, Lucia C. (Jornal de pediatria, 2021)
To develop and validate an instrument about nutritional knowledge and feeding practices to be used in children aged 7–11 years, based on the latest Brazilian Food Guide. Review on the subject; instrument creation; content validity with two groups of judges: first, nutritionists and, after adjustments, a multidisciplinary group (content validity index [CVI]); FACE validity; reproducibility analysis (intraclass correlation coefficient [ICC], level of agreement, and kappa [k]); internal consistency analysis (Cronbach's alpha[α]) and construct validity (Kaiser–Meyer–Olkin and exploratory factorial analysis). The sample was calculated, considering at least ten subjects for each question of the questionnaire. There was a final sample of 453 children (53.6% girls), with a mean age of 9.45 years (SD = 1.44). The content validity showed a CVI ≥ 0.80 for relevance in 62.3% of the items for nutritionists’ group and 100% of the items for the multidisciplinary group, clarity (49.4%, 91.8%), and pertinence (58.8%, 98.4%), respectively. The test-retest showed a level of agreement of 84.3% and k = 0.740 for the Knowledge dimension and ICC = 0.754 for the Food Practices dimension. The internal consistency showed α = 0.589 for the Knowledge dimension and α = 0.618 for the Food Practices dimension. For the construct validity, Kaiser–Meyer–Olkin was 0.724 and exploratory factorial analysis showed a variance of 47.01 with varimax rotation and defined five factors for the Practices Dimension. The Food Knowledge and Practices Questionnaire (Questionário de Conhecimento e Práticas Alimentares [QCPA]) instrument showed validity and reliability to assess nutritional knowledge and food practices in children aged 7–11 years.